Incidence Rates of Arterial Occlusive Acute and Atherosclerotic Chronic Mesenteric Ischaemia: A Population Based Study Over a 15 Year Period - Bako, Eszter; Pengermä, Pasi; Palm, Erik; Saari, Petri; Venesmaa, Sari; Halonen, Jari; Karjalainen, Jari; Kärkkäinen, Jussi M. (Elsevier, 2026)
Objective
To determine contemporary incidence rates of acute mesenteric ischaemia (AMI) and chronic mesenteric ischaemia (CMI).
Methods
A single centre retrospective population based study. The study cohort included patients treated for AMI or CMI between 2009 and 2023 who lived in a well defined region of 250 000 inhabitants in Eastern Finland. Incidence rates with 95% confidence intervals (CIs) for arterial occlusive AMI and CMI were calculated, and stratified by age, sex, and aetiology. Age standardised incidence rates were compared between the sexes using indirect method. Venous and non-occlusive mesenteric ischaemia and median arcuate ligament syndrome were excluded.
Results
Within the study cohort, 141 patients had arterial occlusive AMI. Forty two patients (29.8%) had embolic AMI (15; 35.7% males and 27; 64.3% females) and 99 (70.2%) thrombotic AMI (50; 51% males and 49; 49% females). Fifty three patients had CMI due to atherosclerotic mesenteric artery disease (17; 32% males and 36; 68% females). The incidence rate of occlusive arterial AMI was 3.7/100 000 persons/year (95% CI 3.2 – 4.4) and 1.4/100 000 persons/year (95% CI 1.1 – 1.8) for CMI. In the population aged ≥ 70 years, the incidence rates were 18.4/100 000 persons/year (95% CI 15.1 – 22.1) for AMI and 7.0/100 000 persons/year (95% CI 5.1 – 9.4) for CMI. The incidence rates of embolic AMI and CMI in females were nearly twice as high as in males, whereas no sex related differences were observed in the incidence rates of thrombotic AMI. However, age standardised incidence rates did not statistically significantly differ between the sexes. There were three cases of embolic AMI, three cases of thrombotic AMI, and no cases of CMI in patients aged < 60 years.
Conclusion
It is important to recognise AMI as a potential cause of acute abdominal pain in elderly emergency room patients. The incidence of atherosclerotic CMI was lower than previously reported.